2017
DOI: 10.18203/2320-1770.ijrcog20170405
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of saline infusion sonography as compared to hysteroscopy in premenopausal women with abnormal uterine bleeding

Abstract: Background: In patients with abnormal uterine bleeding (AUB), differentiating whether the cause is anovulation or anatomic lesions can be challenging. Transvaginal sonography (TVS) has limitation in form of high false negative rate for diagnosing focal intrauterine pathology. To improve the image in TVS, saline injected into uterine cavity can be used as a negative contrast agent. Aim of our study was to evaluate the clinical value of saline infusion sonography (SIS) by comparing its diagnostic accuracy with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Many studies have been carried out to compare SIS and HS in evaluating intrauterine abnormalities in several populations. 6,12,13,16 The present study done for the first time in a sub-Saharan population, determined the overall sensitivity, specificity and accuracy to be 81.2%, 86.7% and 86.5% respectively. Similar data have been found by Draz et al with an overall sensitivity of 85%, specificity of 100% and accuracy of 94%.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Many studies have been carried out to compare SIS and HS in evaluating intrauterine abnormalities in several populations. 6,12,13,16 The present study done for the first time in a sub-Saharan population, determined the overall sensitivity, specificity and accuracy to be 81.2%, 86.7% and 86.5% respectively. Similar data have been found by Draz et al with an overall sensitivity of 85%, specificity of 100% and accuracy of 94%.…”
Section: Discussionmentioning
confidence: 61%
“…12 In the same vein, Tangri et al had both sensitivity and specificity at 88% in their study of 136 infertile women. 6 The previous ones conclude that SIS can be a compromise alternative to HS when this later is not available, thus going in the same line of present African context where HS is still very rare. Summarizing, Seshadri et al in their meta-analysis found that the pooled sensitivity of SIS in the detection of all intrauterine abnormalities was 0.88 (95% confidence interval (CI): 0.85-0.90).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Focal lesions are more likely to be missed at routine endometrial biopsy because of sampling error and are under diagnosed at trans vaginal sonography (TVS) because of limitations of the double-layer thickness evaluation. [5][6][7][8] Saline infusion sonohysterography (SIS) is a technique that involves placing a catheter into the uterine cavity through the cervical os to inject 5-20ml of sterile saline into the endometrial canal. The saline distends the cavity, pushing the opposed walls of the endometrium apart.…”
mentioning
confidence: 99%